Một phương pháp xử lí các biểu thức số học trong các hệ trợ giúp tính toán không cần lập trình - Kiếm, Hoàng; Quyền, Nguyễn Mạnh (Journal of Computer Science and Cybernetics, 2016)
This paper deals with the programming techniques for numeric string processing in the mathematical tutor systems. The keys of the method is a technique to sparse basic parts of the numeric string. Some applications in implementation of this method are given.